2019
DOI: 10.1111/clr.13460
|View full text |Cite
|
Sign up to set email alerts
|

Strontium‐incorporated titanium implant surface treated by hydrothermal reactions promotes early bone osseointegration in osteoporotic rabbits

Abstract: Objectives The aim of the present study was to investigate the effects of strontium‐modified implant surfaces on promoting early bone osseointegration in osteoporotic rabbits. Materials and methods The surface topographies, chemical elements, contact angles and ionic releases of the SLA and SLA‐Sr samples were analysed by special instruments separately. Sixteen ovariectomized New Zealand rabbits received glucocorticoid administration, and sixteen SHAM rabbits were used as controls. After generating a successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 63 publications
6
29
0
1
Order By: Relevance
“… 57 The observed short-term bone healing effects of strontium were also in agreement with the Lin et al 50 study, which demonstrated that strontium-modified surfaces induce early osseointegration in rabbits. 50 …”
Section: Discussionsupporting
confidence: 87%
“… 57 The observed short-term bone healing effects of strontium were also in agreement with the Lin et al 50 study, which demonstrated that strontium-modified surfaces induce early osseointegration in rabbits. 50 …”
Section: Discussionsupporting
confidence: 87%
“…in the previous animal experiment in rabbits (Lin et al, 2019). At 8 weeks after implantation, SLA-Sr implant surfaces also displayed better osseointegration in diabetic rats, but there was no difference between two surfaces in the normal group.…”
Section: Discussionmentioning
confidence: 54%
“…Hydrothermal treatment 18,19 Chemical reactions that take place in a liquid phase at high temperature Simple; economical, effective; environmentally friendly; uniform thickness of the deposited layer Some substances are heat-sensitive PIII 20,21 A material engineering process by which ions are accelerated in an electrical eld and impacted onto the surface of a substrate to change the surface chemistry Suitable for processing implants with complex shapes Technical complexity; high costs; high dissolution rate Micro-arc oxidation 22,23 Arc discharge is used to enhance and activate the reaction on the anode, which produces a thick and relatively stable oxide lm on the surface of the metal and its alloy Multi-microporous structure can achieve long-term stable release of metal ions; corrosion-resistant…”
Section: Methods Denition Advantages Disadvantagesmentioning
confidence: 99%
“…17 The performances of different surface modication techniques used for the incorporation of metallic ions are summarized in Table 2. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this paper, we review the adverse effects of metal ions on osseointegration and highlight the emerging applications for metal elements in improving the performance of dental implants.…”
Section: Introductionmentioning
confidence: 99%